The learn smart system: system for people with disability - Urombo, Emmanuel Aaron (Midlands State University, 2019)
This document was produced as part of the final (forth) year project for the BSc. (Hons) Information Systems Degree program. The project was done to present and develop an effective way to enhance the technology utilisation to the individuals with different disabilities at different levels in the education sector. The project involves five basic phases namely introduction phase, planning phase, analysis phase, design phase and the implementation phase. The introduction phase introduces the basis of the project by identifying the existing challenges, information needs in the sector and provide proactive actions in meeting the needs. Planning phase focuses on analysing the feasibility and potential risk involved in the project in order to produce a project plan. The analysis phase identifies the users’ requirements of the system and analyses the system improvement and development opportunities. Design phase is aimed at designing a new system which address the information needs of the organisations in this sector. The final stage (implementation phase) aims to put into effect the new system’s design into its real working environment. Also included in this document are some of the important additional materials utilised in this project and useful material for the system’s description. This was determined to be a feasible idea and the systems strength was on the weaknesses of the related currently existing systems.